China in the 20th century [videorecording]
This program tells the fascinating story of how China made the transition from a medieval empire to a modern state in less than a century. It recounts the violet upheavals the plagued the Chinese people for decades until they were replaced, rather suddenly in recent years, by prosperity ans stability.